Neubau Atmospheres East German Cultural Remediations of Modernist Architecture - Ehrig, Stephan (Oxford Berghahn Books, Incorporated, 2025)
List of FiguresAcknowledgmentsNotes on TranslationIntroduction: Aufbau, Ankunft, Alltag, Neubau.Experiencing and Remediating East German Modernist ArchitectureSECTION I: GENDER & CLASSChapter 1. Genesis of the New Town EverydayChapter 2. Halle-Neustadt PolyphonyChapter 3. Female Urban Planning, Walking, and DesireSECTION II: CHILDREN & YOUTHChapter 4. Appropriating the Unfinished Modernist New TownChapter 5. Obsolescence and the Museal GazeChapter 6. The Fischerinsel Trilogy Afterword: Shifting Gazes and PerceptionsBibliographyIndex
E-Book / Zugriff nur im Lesesaal